The Application of Zakat in Islamic Law to Reduce Economic Inequality in Society - Hermawan, Dadang (Doctoral Program of Social Science Pasundan University, 2025)
Zakat is one of the pillars of Islam that plays a significant role in the economy, particularly in reducing economic inequality and fostering social welfare. This study aims to analyze the application of zakat in Islamic law in North Cikarang, Bekasi, and its impact on reducing economic disparities in society. The research uses a qualitative approach with a case study on several zakat institutions operating in the area. The findings show that effectively managed zakat can have a positive impact in assisting underprivileged communities; however, challenges remain in terms of optimal distribution and management. Factors such as the lack of public understanding of zakat and the limited facilities and resources of zakat institutions become significant barriers in achieving the goal of reducing economic inequality. Despite this, zakat given to the community can be utilized for business capital, education, and healthcare, which in turn contributes to improving the quality of life. Therefore, enhanced coordination between the government, zakat institutions, and the public is necessary to maximize the potential of zakat in reducing economic inequality and achieving social justice in North Cikarang. This research is expected to provide deeper insights into the effectiveness of zakat as a tool for attaining more equitable economic welfare